The temple in early Christianity : experiencing the sacred - Regev, Eyal (Yale University Press, 2019)
"The first scholarly work to trace the Temple throughout the entire New Testament, this study examines Jewish and Christian attitudes toward the Temple in the first century and provides both Jews and Christians with a better understanding of their respective faiths and how they grow out of this ancient institution. The centrality of the Temple in New Testament writing reveals the authors' negotiations with the institutional and symbolic center of Judaism as they worked to form their own religion." -- Publisher description.
Keywords: Temple of Jerusalem (Jerusalem); Temple of Jerusalem (Jerusalem) -- In the Bible.; Bible. -- New Testament -- Criticism, interpretation, etc.; Temple de Jérusalem (Jérusalem); Bible. -- Nouveau Testament -- Critique, interprétation, etc.; Bible. -- New Testament; Christianity -- Early works to 1800.; RELIGION -- Biblical Studies -- Old Testament.; RELIGION -- Judaism -- Sacred Writings.; RELIGION -- Biblical Studies -- History & Culture.; Temple of Jerusalem (Jerusalem) in the Bible; Christianity; Early works; Criticism, interpretation, etc.